The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1139/y86-005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in colonic myoelectric spiking activity during stimulation by bisacodyl

Abstract: The purpose of this study was to determine some relationships between colonic myoelectric spiking activity and intraluminal propulsion when colonic peristalsis was stimulated by bisacodyl. Myoelectric recordings were obtained in 12 subjects by means of a 50 cm long Silastic tube equipped with four bipolar electrodes fixed at 10-cm intervals. The tube was introduced into the left colon by flexible sigmoidoscopy and the electrodes were located at 50, 40, 30, and 20 cm from the anal verge. A small polyethylene ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“… 2 However, in previous studies, it has been shown that the administration of bisacodyl is a good marker of neuro‐enteric integrity and it has been used to induce HAPC’s and shorten study duration 17 . Although the exact mechanism of action of bisacodyl has not been fully elucidated, bisacodyl has been reported to increase myoelectrical propagating activity, 18 transit in the ascending colon 19 and rectal tone 20 in humans. It has also been shown to decrease expression of aquaporin‐3 resulting in inhibition of water passage from lumen to vascular space in rats, producing diarrhea 21 .…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, in previous studies, it has been shown that the administration of bisacodyl is a good marker of neuro‐enteric integrity and it has been used to induce HAPC’s and shorten study duration 17 . Although the exact mechanism of action of bisacodyl has not been fully elucidated, bisacodyl has been reported to increase myoelectrical propagating activity, 18 transit in the ascending colon 19 and rectal tone 20 in humans. It has also been shown to decrease expression of aquaporin‐3 resulting in inhibition of water passage from lumen to vascular space in rats, producing diarrhea 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of colonic contractility appears worthwhile in patients with slow transit constipation who are being considered for colectomy. In such patients, the preservation of the colon’s response to feeding, 86 cholinergic agonists, 134 or intraluminal bisacodyl 100 , 135 excludes inertia, and argues against pursuing a subtotal colectomy and in favour of conservative measures, including use of motility stimulating agents or pelvic floor retraining.…”
Section: Colonic Motility In Disease: Alterations In the Reservoir Ormentioning
confidence: 99%
“…This agent is available with or without a prescription. Bisacodyl is a contact laxative, which acts on the large intestine to produce strong but brief peristaltic movements [10]. It influences intestinal fluid transport and augments epithelial permeability [11].…”
Section: Discussionmentioning
confidence: 99%